Eviction and civil compensation on riverbank land - Firmansah Firmansah; Sulkiah Hendrawati; Wahyudi Wahyudi (Privietlab, 2026)
The eviction of land along the riverbank in Sukadana Village, Kasemen District, Serang City, has raised legal and social issues, particularly regarding the legality of government actions and the mechanism of providing civil compensation to affected residents. Communities that had occupied the land for decades lost their homes without transparent procedures or adequate compensation. This study aims to analyze the legal basis for eviction and civil compensation, as well as identify the obstacles encountered in its implementation. The research method employed is normative juridical, supported by empirical data analysis. Data were obtained through a literature review of legislation, legal literature, and court decisions, complemented by interviews with affected residents and relevant government officials. The findings indicate that the eviction process did not comply with the applicable legal provisions. Socialization, deliberation, and official notifications were not procedurally carried out. The promised compensation in the form of substitute land was not realized, and the government only offered relocation to public housing, which residents deemed inadequate. The main obstacles to policy implementation include limited regional budgets, regulatory changes from the central government, and political pressure with short-term development targets. In conclusion, a gap exists between legal norms and eviction practices in the field, resulting in violations of residents’ rights. Therefore, improvements are needed in the mechanisms of eviction and compensation to ensure they are more transparent, fair, and in line with the principles of a state based on the law.